Periprocedural Hemoglobin Drop and Contrast-Induced Nephropathy in Percutaneous Coronary Intervention Patients - Lee, Kang Hyu; Lee, Sang Rok; Kang, Kyung Pyo; Kim, Huy Jung; Lee, Sun Hwa; Rhee, Kyoung-Suk; Chae, Jei Keon; Kim, Won Ho; Ko, Jae Ki (Korean circulation journal, 2010)
The development of contrast-induced nephropathy (CIN) is associated with an increased risk of death and late cardiovascular events after percutaneous coronary intervention (PCI). The relationship between CIN and hemoglobin drop has been controversial. The aim of this study was to evaluate the clinical usefulness of periprocedural hemoglobin drop as a nontraditional risk factor for CIN. Five-hundred thirty-seven patients who underwent PCI were divided into 2 groups: Group I (486 patients: patients who did not develop CIN) and Group II (51 patients: patients who developed CIN). All patients were administered iodixanol as contrast media during coronary angiography. CIN is defined as a rise in serum creatinine of >/=25% or >/=0.5 mg/dL above the baseline value within 48 hours after contrast administration. BASELINE CLINICAL AND CARDIOVASCULAR RISK FACTORS WERE NOT SIGNIFICANTLY DIFFERENT BETWEEN THE TWO GROUPS, EXCEPT FOR LOW ABDOMINAL CIRCUMFERENCE (GROUP I : Group II=87.9+/-9.0 cm : 81.2+/-15.1 cm, p=0.024), body weight (Group I : Group II=63.5+/-10.6 kg : 59.7+/-9.2 kg, p=0.008), body mass index (BMI) (Group I : Group II=24.4+/-3.4 kg/m(2) : 23.4+/-2.8 kg/m(2), p=0.032), pre-PCI hemoglobin (Group I : Group II=13.2+/-2.0 g/dL : 12.3+/-2.0 g/dL, p=0.003), and post-PCI hemoglobin (Group I : Group II=12.4+/-1.9 g/dL : 11.5+/-1.8 g/dL, p=0.001). Multiple logistic regression analysis showed that a periprocedural drop in hemoglobin (>1 g/dL) was an independent predictor of CIN, like other known risk factors. A periprocedural drop in hemoglobin of more than 1 g/dL is another important independent predictor for CIN, even in patients administered the lowest nephrotoxic contrast agent, iodixanol, during PCI.